Cross sectional observation of the effects of carbon disulphide on the nervous system, endocrine system, and subjective symptoms in rayon manufacturing workers. Issue 7 (July 1998) - Takebayashi, T; Omae, K; Ishizuka, C; Nomiyama, T; Sakurai, H
Abstract : OBJECTIVES: A prospective cohort study was initiated to clarify whether the current level of exposure to carbon disulphide (CS2) is low enough to prevent occurrence of subclinical health impairments or to ameliorate health effects due to past high exposure. This paper describes the effects of exposure to CS2 on the nervous and endocrine systems, and the subjective symptoms in a baseline observation. METHODS: The effects were evaluated of CS2 on the median nerve conduction velocity, neurobehavioural and psychological tests, and subjective symptoms related to solvents in 432 male workers exposed to CS2 and 402 reference workers from 11 rayon factories in Japan. Adjustment was made for potential confounding factors such as age or alcohol drinking. Exposure to CS2 was either dichotomised or categorised into three groups by job type. RESULTS: Reductions were observed in motor (-1.9 m/s) and sensory (-0.91 m/s for orthodromic and -1.1 m/s for antidromic) nerve conduction velocities in the workers exposed to CS2 at the spinning and refining processes. Small but significant increases were found in self rated depression scale score and decrease in digit span (backward) in the workers exposed to CS2. Of 54 subjective symptoms many were increased--namely, heavy feeling in the head, light headedness, fainting after suddenly standing up, tremor, dullness, and increased sensitivity of skin in the extremities, reduced grasping power, reduced sexual desire, and increased rough skin. The endocrinological indicator--the concentration of glycosylated haemoglobin--was also increased in the workers exposed to CS2. CONCLUSIONS: Subclinical effects on the nervous system and on glucose metabolism were found in the workers exposed to CS2. One interpretation is that relatively higher exposure to CS2 in the past may induce these, but the effects are still not entirely ameliorated under the current exposure to CS2. Another possibility is that the current exposure to CS2 may cause these positive findings. A follow up observation is necessary to clarify these questions.